The Challenges of Microentrepreneurship Tourism as a New Tourism Destination in Surabaya - Dian Yulie Reindrawati (Universitas Airlangga, 2020)
This research is conducted due to the existence of new tourism destinations in Surabaya, such as Taman Cahaya, Taman Harmoni and Mangrove Gunung Anyar. The existence of the tourism destinations above gives positive impacts on the community to participate in providing the tourism industry through tourism microentrepreneurship. The objective of this research is to explore the challenges from microentrepreneurship in running the business as a new tourism destination. The method used in this research is qualitative research method with descriptive approach. According to the research results, it is concluded that a new tourism is able to create new opportunities to the community to start a new business with the ideas that the development of tourism will result to more visitors and more money spent by them in the tourism destination. This shows that tourism sector is able to increase the opportunities in starting and developing their own business. The challenges in running microentrepreneurship in tourism areas are influenced by various factors, such as lack of awareness in learning and developing the knowledge with regards to the current business and the business products have not been partnering with online transportation companies in their products development. In Mangrove area, the management of the business vendors seems not well-managed as it can be seen from the absence of food corner and stalls, instead, street vendors are dominating the area. This issue is caused by the lack of financial as well as service supports both from the government and private sectors. The tourism development is considered as the best solution in the tourism area in order to accommodate the tourist needs. As a result, more tourists will visit the area and it will enable the community around the area to increase their economic level. The supports from government and private sectors are also needed to educate microentrepreneurship in developing and promote their products widely.